Precise measurement of intradermal fluid delivery using a low activity technetium-99m pertechnetate tracer - Ranamukhaarachchi, Sahan A.; Esposito, Tullio V.; Raeiszadeh, Mehrsa; Häfeli, Urs O.; Stoeber, Boris (Vaccine, 2019)
•Novel, precise method to assess intradermal (ID) fluid delivery capacity of devices.•Hypodermic needles and hollow microneedles evaluated ex vivo and in vivo.•Captured fluid injected/backflow at high sensitivity compared to gravimetric methods.•Use of low 99mTcO4− radioactivity provided sub-nanoliter measurement resolution.•ID delivery device development facilitated by 99mTcO4− injections. A method was developed and validated to determine the intradermal (ID) fluid delivery potential of several ID devices, including hollow microneedles. The novel method used water soluble technetium-99 m pertechnetate (99mTcO4−) diluted in normal saline to measure the volume of fluid delivered to and remaining in the skin. The fluid that back-flowed to the skin surface and the fluid left on the device surface were also quantified, thus capturing all fluid volumes deposited during intradermal injections. The technique described in this manuscript was used to assess the injection performance of conventional hypodermic needles and hollow microneedles ex vivo using porcine skin and in vivo with a rat model. Since only a small fraction, 1.1%, of the water-soluble tracer remained bound to the skin when applied topically, the technique can be used to differentiate between injected fluid and backflow. Counting of gamma radiation from 99mTcO4− provided sub-nanoliter resolution for volume measurements, making the proposed method powerful, sensitive, and suitable for the assessments of ID injection devices, particularly for vaccine delivery.